2016
DOI: 10.1016/j.ufug.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between neighbourhood tree canopy cover and heat-related ambulance calls during extreme heat events in Toronto, Canada

Abstract: The relationship between neighbourhood tree canopy cover and heat-related ambulance calls during extreme heat events in Toronto, Canada Two thirds of Canadians reside in urban areas and 85% of recent population growth occurs in these areas. The intensity and duration of extreme hot weather events are predicted to increase in Canadian cities and in cities globally. It is well established that human suffering due to extreme heat is exacerbated in urban as compared to rural environments. Understanding the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Human thermal comfort (TC) assessed through heat balance modeling and/or subjective surveys varies across age, sex, activity level, and location, yet few models have examined TC in children and youth during physical activity in outdoor spaces. Outdoor TC is also an essential parameter to assess the value of an outdoor recreational space based on intended use and health benefits (e.g., activity types) [1,2], to improve urban well-being using urban microclimatic design [3], and to guide sustainable urban development [4]. The majority of TC models are based on indoor studies and stem from TC perceptions and physiological parameters of adult subjects [5e7], with little-to-no certainty that the models can be applied to children [8].…”
Section: Introductionmentioning
confidence: 99%
“…Human thermal comfort (TC) assessed through heat balance modeling and/or subjective surveys varies across age, sex, activity level, and location, yet few models have examined TC in children and youth during physical activity in outdoor spaces. Outdoor TC is also an essential parameter to assess the value of an outdoor recreational space based on intended use and health benefits (e.g., activity types) [1,2], to improve urban well-being using urban microclimatic design [3], and to guide sustainable urban development [4]. The majority of TC models are based on indoor studies and stem from TC perceptions and physiological parameters of adult subjects [5e7], with little-to-no certainty that the models can be applied to children [8].…”
Section: Introductionmentioning
confidence: 99%
“…What is less well-known is the variation in distribution of heat-related illnesses across a city and whether the characteristics of a neighborhood has an effect. Graham et al [21] investigated the relationship between physical characteristics of urban areas and the number of emergency medical services (EMS) calls during heat waves in Toronto, Canada. Their results showed that areas with lower tree canopy cover proportions and a higher percentage of hard surfaces corresponded to higher numbers of EMS calls-up to five times higher for areas with very low amount (under 5%) of canopy cover.…”
Section: Reducing Heat-related Illnesses During Heat Wavesmentioning
confidence: 99%
“…and shade are routinely associated with reductions in summertime temperatures and improvements in thermal comfort (TC) [10,11]. Studies performed in Toronto demonstrate 'urban cool islands' [12], as well as associations between canopy cover and emergency response calls [13].…”
Section: Urban Heat Variability and Thermal Comfortmentioning
confidence: 99%
“…The COMFA human EB model is a mathematical model designed to estimate the TC of an individual at a given place and time. Studies have both tested and incorporated revisions into the model to ensure agreement between predicted TC estimates and actual TC responses during both sedentary and non-sedentary activity [13,[48][49][50]. The model requires meteorological inputs (T a , absorbed radiation (R abs ), RH, and V w ) and personal inputs (metabolic activity, M act , and activity velocity, V a ) to produce a human EB in Wm −2 , based on the following summation:…”
Section: Thermal Comfort Case Studymentioning
confidence: 99%
See 1 more Smart Citation